Família e escola: interfaces do atendimento fonoaudiológico de crianças com transtorno de linguagem - Gertel, Marta Cecília Rabinovitsch (2013)
INTRODUCTION: The clinical experience has shown the importance of understanding Family and School in its mutual influence and interdependence in the development of children sent for speech-language therapy. Thinking the relationships between family and school implies to be attentive to the modes by which said instances are related and interfere in the subjective structure and development of a child´s (oral and graphic) language. It also implies to understand that the language disorder, even in the cases it arises from organic events and marks (either congenital or acquired), has the crossed influence of the family and school dynamics, in whose interactions tendencies for the sequence of child´s development is designed. The educational inclusion policy, which has been consolidating in the regular teaching network along the last years, points to the need of integrated actions between school, family and professionals dealing with children presenting language and/or apprenticeships difficulties, said professionals including the speech-language therapist. OBJECT: to present and discuss the pertinence of a speech therapy attention to children with language disorder, by means of an approach that includes the family and the school in the therapeutically process in a simultaneous form and by means of a triangle between speechlanguage therapy events of the child, his/her living experiences, routines and family and school routines. METHOD: This paper bears a clinical-qualitative nature and was designed by means of a reflection based on vignettes selected from clinical case records served by the researcher speech-language therapist, from 2010 to 2011. The utilized material was elaborated along the therapeutically process, from the records appearing in reports obtained from services to children, family and the school. The analysis of clinical material making up the vignettes in the selected cases was supported by the bibliographic review of the thesis, both by speechlanguage literature that considers the family and school dimension in the infantile development, or the conceptual operators inspired in a theoretical reference of Winnicott. For such, two complementary criteria have been followed: the way along the family history axis and the patient´s social-educational axis, and sections of significant moments favoring unfolding in the development of the speech-language therapeutic process. Results: The strategy of simultaneous service to family and school had a direct influence on the therapeutic process of the patients involved in this study. A significant development of each child´s behavior was noticed, mainly concerning the oral and/or graphic communication and the social circulation within the family and school environment. Final considerations: To think the relationships between the child, family and school, as made in this paper, implies to build and enhancing an attention able to apprehend the modes through which said instances go against each other, act in a triangle and interfere in the subjective structuring and development of the child´s (oral and graphic) language. It also assumes that the speech-language therapist is willing to deal with the tensions inherent to said constitutive environments, with the eventual overlapping of roles and functions and with the unavoidable divergences present and expressed about the infantile development. As we understand it, it is for the speech-language therapist to perform the important function of providing the family and the school with a middle way that promotes the acceptance, comprehension and the collaboration with the other, from the foreign perspective. Such mediation, as a willingness to live in the middle of instances and persons in a relationship, is what is liable to benefit and potentialize the child´s development. As the clinical experience has shown, this is possible and very productive in a large part of cases.